PENGARUH KETERGANTUNGAN GADGET TERHADAP KONTROL DIRI SISWA SEKOLAH DASAR - Andi Tenri, A. Tenri Dipa Kurnia; Laurah, Aisyah; Nabila, Dewi Nurul; Anjefin; Asis, Nur Mardania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of gadget dependency on self-control abilities of elementary school students in the digital era, and to propose a program-based solution. The use of gadgets among elementary school-aged children has increased significantly, especially after the Covid-19 pandemic. This research employs a qualitative approach using library research methods, analyzing 15 scientific articles and 5 reference books. The findings indicate that gadget dependency negatively impacts students' self-control, characterized by excessive emotional reactions when gadgets are restricted, reduced learning concentration, weakened social interactions, and decreased self-regulated learning ability. In response to these issues, this study proposes the SMART Program (Schedule, Monitoring, Activity, Rules, Training) as an integrated intervention framework that can be implemented by parents, teachers, and schools to control gadget use wisely and in a structured manner.